Advertising Strategy in Oligopoly Market Competition using Game Theory Approach - Muhammad Abdul Hafizh; Erwin Widodo (Jurnal Teknologi dan Manajemen, 2026)
In oligopoly markets characterized by homogeneous products, producer competition engenders intense rivalry. To prevail over the market, producers employ diverse strategies to boost sales of their respective products, with advertising being a prominent tactic. This strategy aims to augment market awareness of their offerings. This study aims to examine the competitive conduct of producers in oligopoly markets through the lens of game theory. The decision-making scheme under consideration is based on Stackelberg, wherein the leader determines the initial strategy, which the follower then matches. The results of this study indicate that large companies exhibit greater resilience in maintaining their market share compared to small companies. Predatory advertising strategies are found to be effective for companies with large market shares in keeping market dominance. However, for companies with smaller market shares, the adoption of cooperative advertising strategies is recommended to enhance product image without the risk of excessive advertising expenditures